Response to comments on "Fusobacterium and colorectal cancer: causal factor or passenger? Results from a large colorectal cancer screening study": letter to the editor - Amitay, Efrat L.; Brenner, Hermann (Carcinogenesis, 2018)
We would like to thank Dr Güven and Dr Dizdar for their interest in our study ‘Fusobacterium and colorectal cancer: causal factor or passenger? Results from a large colorectal cancer screening study’ and their comments.